1998
DOI: 10.1037/0096-1523.24.4.1232
|View full text |Cite
|
Sign up to set email alerts
|

Laterality in visual speech perception.

Abstract: The lateralization of visual speech perception was examined in 3 experiments. Participants were presented with a realistic computer-animated face articulating 1 of 4 consonant-vowel syllables without sound. The face appeared at 1 of 5 locations in the visual field. The participants' task was to identify each test syllable. To prevent eye movement during the presentation of the face, participants had to carry out a fixation task simultaneously with the speechreading task. In one study, an eccentricity effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 39 publications
(64 reference statements)
2
33
3
Order By: Relevance
“…This is in agreement with previous results on laterality in lipreading [Campbell et al, 1996;Smeele et al, 1998]. Also heard speech is strongly left lateralized in subjects [for review see Tervaniemi and Hugdahl, 2003].…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with previous results on laterality in lipreading [Campbell et al, 1996;Smeele et al, 1998]. Also heard speech is strongly left lateralized in subjects [for review see Tervaniemi and Hugdahl, 2003].…”
Section: Discussionsupporting
confidence: 82%
“…The reported visual field advantages are, however, not fully consistent. Although both left-field (R. Campbell, 1986) and right-field (R. Campbell, de Gelder, & de Haan, 1996) advantages have been observed for static face tasks, a right visual field advantage was reported for silent speechreading (Smeele, Massaro, Cohen, & Sittig, 1998). Two other studies (Baynes, Funnell, & Fowler, 1994;Diesch, 1995) also showed a right visual field advantage for the audiovisual fusion effect provided by incongruent McGurk stimuli such as ours.…”
Section: Resultsmentioning
confidence: 42%
“…Two other studies (Baynes, Funnell, & Fowler, 1994;Diesch, 1995) also showed a right visual field advantage for the audiovisual fusion effect provided by incongruent McGurk stimuli such as ours. Most of these studies used small gaze displacements (,5º from central fixation) and did not directly manipulate stimulus eccentricities, with the exception of Smeele and colleagues (Smeele et al, 1998), who reported a reliable decrease in speechreading performance when the subject's gaze was displaced eccentrically (but within 10º) from the talking face. Although different in design, the small decrease in speechreading performance reported in the latter study is consistent with the effects of gaze fixation position on the perception of the McGurk effect that we observed.…”
Section: Resultsmentioning
confidence: 99%
“…The side of the face that is closest to the display may be an important variable, since this determines whether the visual features well be seen to the right or left of the talking face. There is a large literature on hemifield effects in visual perception and language processing and, although the research is not conclusive (Smeele et al, 1998), it would be advantageous to choose the side that leads to best performance. Thus, we will systematically vary whether the LED display is shown on the left side of the left lens or on the right side of the right lens.…”
Section: Implementing Eyeglasses Appliancementioning
confidence: 99%
“…To obtain information from the face, the perceiver does not have to fixate directly on the talker's lips but can be looking at other parts of the face or even somewhat away from the face [9]. Furthermore, accuracy is not dramatically reduced when the facial image is blurred (because of poor vision, for example), when the face is viewed from above, below, or in profile, or when there is a large distance between the talker and the viewer [5,10,11].…”
Section: Robustness Of Visual Speechmentioning
confidence: 99%